ANALISIS CAMEL DALAM MENILAI TINGKAT KESEHATAN PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - MARSINTA JUNIARTI ARITONANG; HIKMAH . (LP2MTBM MAKARIOZ, 2020)
This study aims to determine the level of banking health in terms of the CAMEL analysis. The design of this research isdescriptive with quantitative research type. The data collection method in this research is the documentation method. Theanalysis technique used in this study is the analysis of bank financial statements. The results showed that a total of 15commercial banks that became the study sample showed